2008
DOI: 10.1186/1743-7075-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and resveratrol inhibit nuclear factor-kappaB-mediated cytokine expression in adipocytes

Abstract: BackgroundAdipocytes express inflammatory mediators that contribute to the low-level, chronic inflammation found in obese subjects and have been linked to the onset of cardiovascular disorders and insulin resistance associated with type 2 diabetes mellitus. A reduction in inflammatory gene expression in adipocytes would be expected to reverse this low-level, inflammatory state and improve cardiovascular function and insulin sensitivity. The natural products, curcumin and resveratrol, are established anti-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(160 citation statements)
references
References 62 publications
(70 reference statements)
9
146
0
Order By: Relevance
“…Another study supported previous findings; they determined that the phospholipid lecithin formulation of standardised curcuminoids (Meriva ® ) increased the curcuminoid absorption up to 29 times as compared to an unformulated curcuminoid mixture, but on the other side with demethoxycurcumin they attained the maximum systemic bioavailability and absorption (Garcea et al 2004). Nevertheless, µg of curcuminoid in plasma remained appreciably less than that required for the inhibition of anti-inflammatory targets identified by curcumin (Gonzales & Orlando 2008). Likewise, Shao et al (2011) synthesised curcumin-loaded spherical core-shell structure nanoparticles composed of methoxy poly(ethylene glycol)-poly block copolymers (mPEG-PCL) in a laboratory.…”
Section: Pharmacokinetics Of Curcuminsupporting
confidence: 73%
“…Another study supported previous findings; they determined that the phospholipid lecithin formulation of standardised curcuminoids (Meriva ® ) increased the curcuminoid absorption up to 29 times as compared to an unformulated curcuminoid mixture, but on the other side with demethoxycurcumin they attained the maximum systemic bioavailability and absorption (Garcea et al 2004). Nevertheless, µg of curcuminoid in plasma remained appreciably less than that required for the inhibition of anti-inflammatory targets identified by curcumin (Gonzales & Orlando 2008). Likewise, Shao et al (2011) synthesised curcumin-loaded spherical core-shell structure nanoparticles composed of methoxy poly(ethylene glycol)-poly block copolymers (mPEG-PCL) in a laboratory.…”
Section: Pharmacokinetics Of Curcuminsupporting
confidence: 73%
“…The IKK/NF-κB inflammatory pathway and TNFα have a critical role in the development of insulin resistance in pathophysiological conditions like obesity 14 . Highfat diet-induced obese rodents presented a significant increase in insulin resistance and expression of inflammatory cytokines, such as IL-1β, IL-6, TNFα, and NF-κB 13 . In states such as insulin resistance, cytokines such as TNFα activate IKKα and IKKβ by intermediate signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Some nutrients increase insulin action significantly 13,14 , such as resveratrol (3,5,4'-trihydroxystilbene), a phytoalexin found in plants and some foods, including peanuts, mulberries, and grapes 15 . Resveratrol provides cardiovascular protection 16 , inhibits platelet aggregation 17 , reduces inflammatory factors 18 , and improves glucose homeostasis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The release of various cytokines after various stimuli from macrophages and lymphocytes, such as IL-6 (Feng et al, 2002;Zhong et al, 1999), IFN , IL-2, TNF-, and IL-12 (Gao et al, 2001), has been shown to be inhibited by resveratrol. Resveratrol was also reported to suppress the activity of T-and B-cells, and macrophages the major cell types responsible for producing cytokines by decreasing the production of proinflammatory proteins, (Sharma et al, 2007) and it was able to reduce TNF-, IL-1 , IL-6, and COX-2 gene expression and to reduce the secretion of IL-6 and PGE2 in TNF--stimulated adipocytes (Gonzales & Orlando, 2008). In an age-related diseases study, mice treated with resveratrol had decreased expression of the inflammatory markers TNF-, IL-1 , IL-6, intercellular adhesion molecule (ICAM)-1 and iNOS (Pearson et al, 2008).…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%